2020
DOI: 10.3389/fphys.2020.00515
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Quality Control and Cellular Proteostasis: Two Sides of the Same Coin

Abstract: Mitochondrial dysfunction is a hallmark of cardiac pathophysiology. Defects in mitochondrial performance disrupt contractile function, overwhelm myocytes with reactive oxygen species (ROS), and transform these cellular powerhouses into prodeath organelles. Thus, quality control (QC) pathways aimed at identifying and removing damaged mitochondrial proteins, components, or entire mitochondria are crucial processes in post-mitotic cells such as cardiac myocytes. Almost all of the mitochondrial proteins are encode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 164 publications
1
40
0
Order By: Relevance
“…The central relevance of the proteasome for aging cells is not limited to neurons, but also well established for the skeletal and cardiac muscle cells of. Owing to their permanent activity, their high energy consumption, and mechanical stress conditions, (cardio)myocytes are indeed particularly vulnerable to proteotoxic stress [13,144,145].…”
Section: Relevance For Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The central relevance of the proteasome for aging cells is not limited to neurons, but also well established for the skeletal and cardiac muscle cells of. Owing to their permanent activity, their high energy consumption, and mechanical stress conditions, (cardio)myocytes are indeed particularly vulnerable to proteotoxic stress [13,144,145].…”
Section: Relevance For Diseasementioning
confidence: 99%
“…There is no doubt that the mitochondrial quality control system is crucial to maintain mitochondrial proteostasis and for the dynamic adaptation of the mitochondrial proteome to changing metabolic conditions [9][10][11][12]. Nevertheless, studies over the past decade have shown that the ubiquitin-proteasome system (UPS) of the cytosol is of pivotal relevance for the surveillance of the mitochondrial proteome [13][14][15][16][17]. Particularly important in this context are the degradation of cytosolic mitochondrial precursor proteins and that of mitochondrial surface proteins, the so-called mitochondria-associated degradation (MAD), by the proteasome.…”
mentioning
confidence: 99%
“…This is in line with our recent study showing that the mitochondrial transcription factor A (TFAM), which is also upregulated after LPS treatment suffers from the same dilemma, namely not reaching the mitochondria [ 17 ]. Taken together, our results hint at an insufficient translocation of mitochondrial proteins that need to be shuttled from the cytoplasm into the mitochondrial matrix [ 18 ]. These results, therefore, underline that when studying mitochondria, the protein abundance within the mitochondria needs to be considered in addition to their cellular expression.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria and endoplasmic reticulum (ER) in cardiomyocytes are overrepresented organelles to co-ordinate the increased metabolic demands and maintain active calcium stores for smooth flow. Endoplasmic reticulum and mitochondria quality control circuits are also integral to cardiac function, and deregulation of these pathways are strongly implicated in cardiac diseases including heart failure [57][58][59][60][61][62][63]. ECM remodeling is emerging to coincide with metabolic rewiring in cardiomyocytes and matrixguided control of mitochondrial function in cardiomyocytes is seen as a potential therapeutic target in cardiac fibrosis, repair, regeneration and tissue engineering [64].…”
Section: Abortive Cellular Homeostasis Rebalancing In Cardiac Fibrosimentioning
confidence: 99%